Incorporação da sustentabilidade em cadeias de suprimentos: práticas estabelecidas e barreiras encontradas - Nascimento, Annelise Mendes (2014)
This research aims to present and analyze the practices that can be established by focus companies with their suppliers, distributors and consumers, so that sustainability is embedded in their supply chains. Moreover, as a way to better understand the dynamics of sustainability, the research also analyzes the barriers faced by organizations when adopting this type of practice. From the information obtained by the technique of systematic literature review, we developed a questionnaire for the empirical stage of this research - a survey with organizations known for adopting sustainable practices. Among the results, it is emphasized that the practices aimed at environmental issues are further explored, both in literature and empirically. Regarding the practices with suppliers, those that require a lesser degree of involvement between companies - less collaboration - and had a more assessment nature stood out. Considering the chain downstream, practices among distributors are still poorly known, both in literature and empirically; and practices that stood out with consumers referred to the sharing of information, and labeling of products. Considering the barriers, the more relevant indicated by respondents was the cost. From the results obtained, proposals were outlined, both theoretical and practical, about the incorporation of sustainable practices throughout the supply chain, and how to overcome potential barriers. It is believed that these proposals can be a starting point for further academic research, and still be used by managers interested in the sustainable management of their organizations.